Endogenous Third-Degree Price Discrimination in a Supply Chain with One Common Manufacturer and Duopoly Retailers - Hongmei Yang; Wei Wang (Discrete Dynamics in Nature and Society)
Assuming the two retailers decide whether to acquire information to segment consumers and price them differently, we investigate the problem of information acquisition and third-degree price discrimination in the supply chain composed of one common manufacturer and duopoly retailers. We explore how the supply chain members’ pricing decisions are affected by the fraction of high price-sensitivity consumers and the consumers’ difference in price sensitivity. Analytical results show that the manufacturer’s wholesale price increases with the fraction of high price-sensitivity consumers and decreases with the consumers’ difference in price sensitivity. Moreover, if a retailer chooses to acquire information and price discriminate, the retail prices for two types of consumers increase with the fraction of high price-sensitivity consumers. However, the retail price for consumers with high (low) price sensitivity decreases (increases) with the consumers’ difference in terms of price sensitivity. By comparing the results among different information acquisition and price discrimination decisions, we find that there exist two possible equilibrium decisions for both retailers: both retailers acquire information and price discriminate and no retailer acquires information and each charges a uniform price for all consumers. The strategy which dominates depends on the fraction of high price-sensitivity consumers and the consumers’ difference in price sensitivity. However, compared with no retailer acquiring information, the manufacturer is better off when two retailers acquire information. Consequently, the manufacturer designs a fixed fee contract to stimulate retailers to price discriminate and to achieve a win-win situation for them finally.